2016
DOI: 10.1186/s12967-016-0871-3
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the gene expression profile of peroxisome proliferator-activated receptor signaling pathway in the left atria of patients with mitral regurgitation

Abstract: BackgroundDifferentially expressed genes in the left atria of mitral regurgitation (MR) pigs have been linked to peroxisome proliferator-activated receptor (PPAR) signaling pathway in the KEGG pathway. However, specific genes of the PPAR signaling pathway in the left atria of MR patients have never been explored.MethodsThis study enrolled 15 MR patients with heart failure, 7 patients with aortic valve disease and heart failure, and 6 normal controls. We used PCR assay (84 genes) for PPAR pathway and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Furthermore, CPT1, which facilitates the transportation of long chain FA into the mitochondrial matrix [34], was also increased by treatment of QSG. ACADL, ACADM, ACAA2 and SCP2, the critical enzymes for β-oxidation of FA within the mitochondria [26][27][28]35], were all upregulated by QSG treatment, indicating that QSG could promote fatty acid β-oxidation.…”
Section: Qsg Promoted Fa Uptake Transportation Into Mitochondria Andmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, CPT1, which facilitates the transportation of long chain FA into the mitochondrial matrix [34], was also increased by treatment of QSG. ACADL, ACADM, ACAA2 and SCP2, the critical enzymes for β-oxidation of FA within the mitochondria [26][27][28]35], were all upregulated by QSG treatment, indicating that QSG could promote fatty acid β-oxidation.…”
Section: Qsg Promoted Fa Uptake Transportation Into Mitochondria Andmentioning
confidence: 97%
“…FAT/ CD36 medicates the entry of long-chain FA into cardiac cells [25], and CPT1 is the rate-limiting enzyme for transportation of FA from cytoplasm to mitochondria [9]. ACADL, ACADM, ACAA2 and SCP2 facilitate the metabolism of FA through β-oxidation in mitochondria [26][27][28]. The protein levels of cardiac FAT/CD36, CPT1A, ACADL, ACADM, ACAA2 and SCP2 were all impressively reduced in the model group compared to the sham group (P < 0.05 or P < 0.01, Fig.…”
Section: Effects Of Qsg On Fat/cd36-cpt1-fao Pathway In Hf Rats Aftermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the results for gene ontology and pathway enrichment analyses of the genes, expressed differentially in that study, revealed PPAR signaling in the KEGG pathway [13]. Additionally, expressions of genes linked to the PPAR signaling pathway, especially genes related to fatty acid β-oxidation, in the left atria of MR patients reportedly differs from patients with aortic valve disease and normal controls [14]. Mitral regurgitation patients also have significantly higher lipid expression of atrial myocytes compared to normal controls [14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, expressions of genes linked to the PPAR signaling pathway, especially genes related to fatty acid β-oxidation, in the left atria of MR patients reportedly differs from patients with aortic valve disease and normal controls [14]. Mitral regurgitation patients also have significantly higher lipid expression of atrial myocytes compared to normal controls [14]. Perturbation of lipid homeostasis due to a fatty acid uptake–utilization mismatch in the heart reportedly leads to the development of lipotoxic cardiomyopathy, an acquired form of cardiomyopathy [12].…”
Section: Introductionmentioning
confidence: 99%